1980
DOI: 10.1126/science.6930106
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Anorexia: A Learned Food Aversion?

Abstract: Anorexia can occur when a specific diet is associated with a developing illness. The studies reported here show that the decline in food intake which accompanies tumor growth is accompanied by the development of aversions to the specific diet consumed during tumor growth. An immediate elevation in food consumption occurred when a novel diet was introduced. Therefore, the development of learned aversions to the specific diet eaten during tumor growth may be a causal factor in the development of tumor anorexia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
2

Year Published

1982
1982
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(30 citation statements)
references
References 16 publications
1
27
0
2
Order By: Relevance
“…Others do not support the above ®nding (Donaldson et al, 1981;Carter et al, 1983b;Besscho 1986;Tamminga et al, 1990). Most clinicians, however, agree that intensive chemotherapy is often associated with a deterioration of nutritional status of the patients (Bernstein & Sigmundi, 1980;Dorr & Fritz 1980;Rickard et al, 1980;Bernstein et al, 1982;Donaldson et al, 1981;Nunnaly, 1983;Keenan 1989;Kennedy & Diamond, 1997;Papadopoulou et al, 1996a).…”
Section: Indications For Bone Marrow Transplantation As Determinants mentioning
confidence: 99%
See 1 more Smart Citation
“…Others do not support the above ®nding (Donaldson et al, 1981;Carter et al, 1983b;Besscho 1986;Tamminga et al, 1990). Most clinicians, however, agree that intensive chemotherapy is often associated with a deterioration of nutritional status of the patients (Bernstein & Sigmundi, 1980;Dorr & Fritz 1980;Rickard et al, 1980;Bernstein et al, 1982;Donaldson et al, 1981;Nunnaly, 1983;Keenan 1989;Kennedy & Diamond, 1997;Papadopoulou et al, 1996a).…”
Section: Indications For Bone Marrow Transplantation As Determinants mentioning
confidence: 99%
“…A recent study in children undergoing BMT reported that oral ondansetron was superior to a combination of antiemetic drugs (perphenazine with diphenhydramine) on conditioning-related emesis control (Mehta et al, 1997). Furthermore, anorexia and low oral intake are also associated with the use of chemotherapy: associations between the taste of foods and tumour growth per se (Bernstein & Sigmundi, 1980), altered taste sensations which are often associated with the use of cyclophosphamide (Nunnaly, 1983), and learned aversions for foods eaten before the administration of chemotherapy may all cause nausea and/or vomiting (Bernstein et al, 1982). Oral mucositis is one of the more common side-effects of chemotherapy (Kennedy & Diamond, 1997).…”
Section: Indications For Bone Marrow Transplantation As Determinants mentioning
confidence: 99%
“…The main identifiable Previous investigations of learned food aversions in tumour humoral products secreted by Leydig cell tumours are bearing rats and patients (Bernstein & Sigmundi, 1980; oestrogens, but Experiment 5 showed that raising the plasma Bernstein & Webster, 1980) did not test food preference for oestradiol concentration of normal rats to a level comparable to that of the tumour bearing animals did not have the same effect on food preference or body composition as tumour growth. If the anorexia and cachexia of cancer are indeed mediated through an as yet unidentified humoral substance it may be that this substance is in fact synthesised by host tissues in response to the presence of the tumour rather than by the tumour itself (Editorial, 1985).…”
Section: Np Throughout Days 2-1o Was the Opposite Of What Wouldmentioning
confidence: 99%
“…We monitored the growth rate, total food intake associate the growth of the tumour with the diet which it has and body composition of the rats to ascertain that this was a consumed during tumour growth, and if it is then offered a suitable model for the anorexia and cachexia of human choice between this diet and a different diet it shows an cancer. In some of the studies we used Sprague-Dawley rats, immediate preference for the new diet (Bernstein & which were more readily available, when we found that the Sigmundi, 1980). The introduction of this new diet also tumour grew equally well in them and had the same effects causes at least a transient increase in total food conon food intake and body composition.…”
mentioning
confidence: 99%
“…These factors were more important in determining quality of life than the ability to work, physical strength or sexual satisfaction (Padilla, 1986). The background to this often profound loss of appetite and the weight loss that accompanies cancer is complex and agreement on the underlying mechanism has not been reached (Bernstein & Symundi, 1980). Psychological, emotional or physiological factors due to the disease and treatment may initiate or worsen anorexia, but as the disease progresses it is usually the cancer itself that is the main cause of the anorexia (Theologides, 1977 (Goodinson, 1987a).…”
mentioning
confidence: 99%